REMNANTS OF QUILOMBOLAS: THE QUILOMBO CALUETE IN GARANHUNS-PE - Cardoso do Farias, Giovane (Revista Gênero e Interdisciplinaridade, 2025)
Based on the observation of the social dynamics of quilombola communities in the Municipality of Garanhuns-PE, this article provides a brief summary of the Master’s Dissertation in Educational Sciences carried out by Veni Creator Christian Universit, whose research focuses on the black community of Caluete, where social and political problems are identified, culminating in discrimination due to territorial location, social, political and religious issues. The people descended from enslaved black Africans still suffer segregation and discrimination similar to the suffering imposed during the slavery period, which is more evident in the aforementioned community, which is located 22 km from the headquarters of Garanhuns, considered distant from the city, as well as from other communities. quilombolas in the municipality, and bordering the municipality of Brejão-PE. In this context, the research has the general objective of investigating the causes that lead Quilombo do Caluete to be neglected by the municipality’s public authorities and, consequently, by the state and federal spheres.